Temperature-dependent high resolution absorption cross sections of propane. (October 2016) - Beale, Christopher A.; Hargreaves, Robert J.; Bernath, Peter F.
Abstract: High resolution (0.005 cm −1 ) absorption cross sections have been measured for pure propane (C3 H8 ). These cross sections cover the 2550–3500 cm −1 region at five temperatures (from 296 to 700 K) and were measured using a Fourier transform spectrometer and a quartz cell heated by a tube furnace. Calibrations were made by comparison to the integrated cross sections of propane from the Pacific Northwest National Laboratory. These are the first high resolution absorption cross sections of propane for the 3 μm region at elevated temperatures. The cross sections provided may be used to monitor propane in combustion environments and in astronomical sources such as the auroral regions of Jupiter, brown dwarfs and exoplanets. Highlights: High resolution (0.005 cm −1 ) cross sections recorded for 3 μm region of propane. First such measurements at high temperature (up to 700 K). May be used to monitor propane in combustion environments or exoplanet/brown dwarf atmospheres.